2022
DOI: 10.1039/d1fo03636j
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α-glucosidase by trilobatin and its mechanism: kinetics, interaction mechanism and molecular docking

Abstract: α-Glucosidase is related to the increase of postprandial blood glucose in vivo. Inhibition of α-glucosidase is supposed to be an effective approach to treat type 2 diabetes mellitus (T2DM). Trilobatin,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…The Lineweaver-Burk plots revealed that the LS extract inhibited α-glucosidase by a non-competitive mechanism with a K i value of 1.32 µg/mL, which is in accordance with a previous kinetic analysis, indicating that trilobatin reversibly inhibited α-glucosidase in a non-competitive manner (He et al. 2022 ). This effect was stronger than that of acarbose, as positive control.…”
Section: Discussionsupporting
confidence: 90%
“…The Lineweaver-Burk plots revealed that the LS extract inhibited α-glucosidase by a non-competitive mechanism with a K i value of 1.32 µg/mL, which is in accordance with a previous kinetic analysis, indicating that trilobatin reversibly inhibited α-glucosidase in a non-competitive manner (He et al. 2022 ). This effect was stronger than that of acarbose, as positive control.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that trilobatin is a strong α-glucosidase inhibitor, which may be beneficial to improve the blood glucose level in DM. 40 However, the fundamental measure to reduce blood glucose fluctuation is to improve the islet function. 41 In our included studies, it has been most commonly reported that DST ameliorates blood glucose and insulin resistance in DM animals, which is also shown in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The double reciprocal fitting curve of the preparation is: (R 2 = 0.9989), the Michaelis constant Km is 0.514, and the maximum rate of enzymatic reaction Vmax is 0.08. In addition, it can be seen from the Figure 6 that the inhibition curves of different horizontal intercepts and slopes intersect at one point with the longitudinal axis, indicating that the inhibitor concentration increases, Km increases, and Vmax remains unchanged, which is the most significant feature of competitive inhibition [ 32 ]. It was also shown that MAP-2 can bind to the active site of α-glucosidase in a reversible manner, thereby inhibiting the decomposition of glycosides into glucose and reducing postprandial blood glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Lactase, also known as β-galactosidase, is one of the important functions of enzymes of the intestinal tract, mainly composed of small intestinal villus and intestinal bacteria secrete of brush border, and closely associated with diarrhea, abdominal distention [ 33 ], and studies have shown that, when the body lacks lactase, the symptoms of lactose intolerance occurs [ 34 ], such as severe diarrhea, abdominal distension [ 32 ], and severe cases can produce dehydration, acidosis and growth disorder, etc. [ 35 ].…”
Section: Resultsmentioning
confidence: 99%